Розробка міні-лінії для виготовлення паливних брикетів - Самойчук, Кирило Олегович; Самойчук, Кирилл Олегович; Samoichuk, Kyryl; Самохвал, Віталій Анатолійович; Самохвал, Виталий Анатолиевич; Samokhval, Vitalii (Мелітополь: ТДАТУ, 2021)
UK: Для вирішення проблем нестачі на ринку України універсальних та енегоефективних міні-ліній для переробки рослинної сировини на високоякісні паливні брикети проаналізовані основні конструкції пресового обладнання. Визначені основні недоліки існуючих промислових ліній. Розроблено міні-лінію для виробництва паливних брикетів, яка суміщає операції очищення, провіювання, пресування сировини і виділення якісної технічної олії. Використання лінії дозволяє зменшити енерговитрати до 6,5–7,0 кВт при продуктивності до 5 т/добу шляхом створення умов для холодного пресування сировини з виділенням якісної технічної олії. RU: Для решения проблем нехватки на рынке Украины универсальных и энегоэффективных мини-линий для переработки растительного сырья на высококачественные топливные брикеты проанализированы основные конструкции прессового оборудования. Определены основные недостатки существующих производственных линий. Разработана мини-линия для производства топливных брикетов, которая совмещает операции очистки, провеивания, прессования сырья и выделение качественного технического масла. Использование линии позволяет уменьшить энергозатраты до 6,5-7,0 кВт при производительности до 5 т/сутки путем создания условий для холодного прессования сырья с выделением качественного технического масла. EN: Briquetting is a necessary operation in various industries, which reduces the cost of storage and transportation of raw materials. The main problems in the production of fuel briquettes from vegetable raw materials are high energy consumption for the operation of press equipment and the lack of universal mini-lines in the Ukrainian market for processing vegetable raw materials into high-quality fuel briquettes. To solve these problems, the basic designs of press equipment are analyzed. It is established that the main disadvantages of the existing industrial lines are the increased energy consumption due to the need to preheat the pressed mass and the low yield of oil or resins from the raw material, which increases the amount of harmful substances in the briquette. The main requirements for an energy-efficient mini-line for the production of fuel briquettes are defined. The main goal in the development of the line is to obtain a high-quality product with the ability to separate oil raw materials and low specific energy consumption. A mini-line for the production of fuel briquettes has been developed, which combines the operations of cleaning, screening, pressing of raw materials and the allocation of quality technical oil. The presented line is capable of processing such types of vegetable raw materials as: wood processing waste, waste of sunflower, soybean, flax, rape. It is possible to simultaneously squeeze the technical oil and adjust the temperature of the briquette during pressing, which significantly expands the range of raw materials that can be used for processing. Tests of the line showed the possibility of making briquettes from waste scraping sunflower, coriander, flax and soybeans and wood waste with a density of 1300-1500 kg/m3. The temperature of the briquette at the outlet of the press extruder does not exceed 80 0C. Screw speed 70–85 rpm. Steady-state power is 6.5–7.0 kW with a capacity of up to 5 t/day. Specific energy consumption is up to 40 kW / t.
Разработка мини-линии для изготовления топливных брикетов
Development of mini-line for manufacture of fuel briquettes
Keywords: брикетування; холодний віджим; шнековий прес; прес-еструдер; паливні брикети; брикетирование; холодный отжим; шнековый пресс; пресс-еструдер; топливные брикеты; briquetting; cold pressing; screw press; press extruder; fuel briquettes